Development and uptake of the National Heart Foundation of Australia Smart Heart Guideline App. (14th October 2021) - Atkins, B; Matthews, S; Walton, N; Mitchell, J; Battaglia, T; Muir, T; Jennings, G L R; Buttery, A K
Abstract: Background: Many organisations have developed Smartphone mobile applications (apps) to improve access and uptake of clinical guidelines, including the European Society of Cardiology and the American Heart Foundation. The National Heart Foundation of Australia publish clinical guidelines in collaboration with the Cardiac Society of Australia and New Zealand. We aimed to develop an app for three national guidelines: 1) the Australian clinical guidelines for the prevention and detection of atrial fibrillation 2018; 2) the Australian clinical guidelines for the detection and management of heart failure in Australia 2018; and 3) the Australian clinical guidelines for the management of acute coronary syndromes 2016. Purpose: To develop a mobile app for Australian health professionals to improve access and uptake of national cardiac clinical guidelines. Methods: A national health professional mobile app online survey was developed and distributed in 2017. Survey items included the frequency of searching for information about the prevention or management of cardiovascular disease, the methods of searching, and the likelihood of using an Australian-specific mobile app to access clinical guidelines. Following analysis of survey responses, a software developer was contracted to develop the app, which included user-testing. The Smart Heart Guidelines App was registered with the regulatory body in Australia, the Therapeutic Goods Administration, and made freely available from October 2019 on iOS and Android operating systems. The app was promoted using electronic direct mail, social media techniques (Twitter and LinkedIn), on our organisation's website and via printed flyers and materials at regional and national event stands at conferences. Data from the Apple App Store was analysed between 1 October 2019 – 1 October 2020 to evaluate app use. Results: The health professional survey (respondents n=504; nurses 39%, allied health professionals 26%; GP/cardiologist 9%; researcher 8%; other 18%) showed most (n=447; 89%) reported accessing the Heart Foundation's resources electronically. The majority (n=355; 70%) reported they would be likely to use an Australian-specific app. Data from the Apple App Store indicated over 30, 300 impressions (the number of times the Smart Heart App appeared in an App Store search) during the first year the app was available. This resulted in approximately 4, 400 app downloads, with consistent "search-to-download rates" throughout the year (monthly average rate 22%). Of the downloads, 3, 200 (82%) were a direct result of searching for the Smart Heart App, indicating promotional activities were effective. Conclusion: Development of the Smart Heart Guideline App in Australia was indicated by health professionals to improve access to national cardiac clinical guidelines. Consistent app downloads and use during the first-year support further research, development, promotion, and evaluation of the app. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The National Heart Foundation of Australia